Pasantías en La Dirección de Impuestos y Aduanas Nacionales en la Subdirección de Gestión de Control Cambiario (2025)
To have a closer approximation to what the Tax Directorate represents and National Customs (DIAN) at the national level in customs, exchange and tax matters; HE proceeds to make a global story, for the knowledge of this entity. From the general to the particular, in this sense, what is relevant would be the Management Customs Section in charge of Supervision and Exchange Settlement and Others Violations where the internship will take place.